Physical Mechanisms Driving Oxygen Subduction in the Global Ocean - Portela, Esther; Kolodziejczyk, Nicolas; Vic, Clément; Thierry, Virginie (Geophysical Research Letters, 2020)
International audience Future changes in subduction are suspected to be critical for the ocean deoxygenation predicted by climate models over the 21st century. However, the drivers of global oxygen subduction have not been fully described or quantified. Here, we address the physical mechanisms responsible for the oxygen transport across the late-winter mixed layer base and their relation with water mass formation. Up to 70% of the global oxygen uptake takes place during Mode Water subduction mostly in the Southern Ocean and the North Atlantic. Te driving mechanisms are (i) the combination of strong currents with large mixed-layer-depth gradients at localized hot spots and (ii) the wind-driven vertical velocity within the subtropical gyres. Oxygen diffusion, despite being underestimated in this study, is likely to play an important role in the global ocean oxygenation. The physical mass flux dominates the total oxygen subduction while the oxygen solubility plays a minor role in its modulation.